Using Team-Based Learning to Teach Pharmacology within the Medical Curriculum - Nora L. D. Luitjes; Gisela J. van der Velden; Rahul Pandit (MDPI AG, 2024)
The primary goal of pharmacology teaching is to prepare medical students to prescribe medications both safely and efficiently. At the Utrecht University Medical School, pharmacology is integrated into the three-year bachelor's curriculum, primarily through large group sessions with limited interaction. A recent evaluation highlighted students' appreciation for pharmacology teaching, but students admitted to attending these teaching moments unprepared, resulting in passive learning. To address this, team-based learning (TBL) was implemented to facilitate learning through interaction, critical thinking, problem solving and reflection through six steps, from superficial to deeper cognitive learning. This study, conducted over two academic years, assessed students' perception and performance regarding TBL. Analysis of a digital questionnaire using a 5-point Likert scale showed high student satisfaction with TBL as a teaching methodology. However, confidence in pharmacology knowledge following TBL was moderate. TBL attendees outperformed non-attendees in pharmacology-related exam questions, indicating that TBL has a positive impact on student performance. We conclude that TBL is an engaging and effective method for pharmacology education, positively influencing student learning and performance. This method could be broadly applied for teaching pharmacology within the medical curriculum or other biomedical programs.